Pengaruh Umur Perusahaan, Persentase Saham Yang Ditawarkan Dan Reputasi Underwriter Pada Saat Initial Public Offering (IPO) Terhadap Underpricing Saham di Bursa Efek Indonesia (BEI) Tahun 2016-2021 - P, Nina Meisya.; Harmain, Hendra; Armayani, Rini Ria (Universitas Labuhanbatu, 2023)
This research aims to analyze how much influence the age of the company, the percentage of shares offered and the reputation of the underwriter at the time of the Initial Public Offering (IPO) has on the underpricing of shares on the Indonesia Stock Exchange (BEI) in 2016-2021. The research method used is a quantitative descriptive approach. The type of data used is secondary data. A sample of 232 companies was obtained using the purposive sampling method and the SPSS version 23 test tool. The results of the research show that the first t test on company age has a positive and significant effect on stock underpricing with a t value of 2.012 with a sig value. 0.023. Both percentages of shares offered have a positive and significant effect on share underpricing with a t-count of 2,882, with a sig value of 0.004. The three underwriter reputation variables have a negative and significant effect on stock underpricing with a t value of -3.181 and a sig value. 0.002. And the four F-statistic test results show that the variables company age, percentage of shares offered and underwriter reputation simultaneously have a significant effect on share underpricing during the Initial Public Offering on the IDX in 2016-2021 with a sig value. 0.000 < 0.05. The test results show that the variables of company age, percentage of shares offered and underwriter reputation contribute 83% to the share underpricing variable.